Chamber music for rock festivals: textural references to progressive rock in Ketil Hvoslef’s Konsert for violin og pop-band (1979) (Música Hodie, 2023)
Abstract: Konsert for violin og pop-band is an example of the appropriation of a popular music genre within western art music. By means of instruments such as the electric guitar, this composition presents progressive rock textures that function as a genre synecdoche. This article presents a perceptual and semiotic analysis of this work to determine the characteristics of these textures and the connotations that they contribute. This is supported by the study of its cultural context and the different audiences it is intended for, from its premiere at a rock festival to its survival within the chamber music scene.